MRKH syndrome: a review of literature - Jain, Nidhi; Kamra, Jyotsna Harlalka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Primary amenorrhea is defined as failure to achieve menarche till age of 14 years in absence of normal secondary sexual characters or till 16 years irrespective of secondary sexual characters. The most common cause of primary amenorrhea is gonadal pathology followed by Mayer-Rokitansky-Küster-Hauser syndrome (MRKH syndrome). MRKH syndrome is a rare congenital disorder characterised by uterine and vaginal aplasia. It occurs due to failure of development of Müllerian duct. Its incidence is 1 per 4500 female births. Mostly girls present with primary amenorrhea. It is characterised by presence of normal secondary sexual characteristics, normal 46 XX genotype, normal ovarian function in most of the cases and absent or underdeveloped uterus and upper part (2/3) of vagina. It is of two types: type A is isolated type while type B is associated with other renal/skeletal/cardiac anomalies. Treatment includes psychological counselling and vaginoplasty. Vaginoplasty can be done by various non-surgical and surgical techniques. The authors hereby review the literature of MRKH syndrome regarding its embryology, etiopathogenesis, approach to work up and management.